Cytogenetic and histological studies of the brook trout (Salvelinus fontinalis) x arctic charr (Salvelinus alpinus) hybrids - Lisboa, Rodrigo (2012)
In aquaculture, application of fish hybrids has increased. This technique permits improvement of the fish production by providing specimens showing better growth rate when compared to the parental species. Indeed, sterile individuals are highly demanded because quite frequently parental fish mature before they reach the market size, which impairs their growth and decrease their economic value. Throughout the last years, the commercial and scientific interest in salmonids has increased rapidly, among them, the brook trout (Salvelinus fontinalis), Arctic charr (Salvelinus alpinus) are species that can be crossed to produce hybrids that might by cultured in the fish farms. In the present thesis, we have assessed chromosome numbers and evaluate gonadal sex in the brook trout X Arctic charr hybrid progenies. In our populations, the karyotype of the brook trout comprises 84 chromosomes: 16 bi-armed chromosomes (meta-submetacentric) and 68 one-armed chromosomes (telo-acrocentrics) and the chromosome arm number, NF= 100. Arctic charr karyotype shows variation related to the chromosome number (2n= 81-82) and stable chromosome arm number (NF= 100). 2n= 81 chromosomes consisted of 19 bi-armed and 62 one-armed chromosomes, while 2n= 82 karyotype was organized into 18 meta-submetacentric and 64 acrocentrics. The cytogenetic and histological analysis of the brook trout X Arctic charr hybrids (sparctics) was carried out to asses chromosome and chromosome arm number and gonadal sex of the studied specimens. Diploid chromosome number in the hybrids varied from 81 to 84 and individuals with 83 and 84 chromosomes were predominant. Most of the fish had chromosome arm number equal to 100. Robertsonian fusion in the Arctic charr and chromosome behaviour in the hybrid fish cells might lead to the observed variation in chromosome numbers in the hybrids. Among studied fish, 12 were males, 3 were females and 9 had intersex gonads. No correlation between chromosome number and disturbances in the gonadal development was found. This might suggest that intersex gonads might have been developed as a consequence of disturbances in the genetic sex determination process. Genetic sex determination acts properly in the parental species but in the hybrids this may not be as efficient.